Persistence and nutrients release of forage turnip straw utilized as mulching in no-tillage crop system - Crusciol, Carlos Alexandre Costa; Cottica, Roberto Luiz; Lima, Eduardo do Valle; Andreotti, Marcelo; Moro, Edemar; Marcon, Edílson (Pesquisa Agropecuaria Brasileira, 2005)
Straw of covering plants kept on soil surface in no-tillage system is an important source of nutrients for subsequent tillage. The objective of this work was to evaluate decomposition and macronutrients release from forage turnip residues. The experiment was set under field conditions during 1998 in Marechal Cândido Rondon, PR, Brazil. Forage turnip plants were desiccated and lodged 30 days after emergence. Straw persistence and nutrient release were evaluated at 0, 13, 35 and 53 days after management. The experimental design was a randomized block with four replications. Until pre-flowering stage, the forage turnip showed a great dry matter yield (2,938 kg ha-1) during winter growing and 57.2, 15.3, 85.7, 37.4, 12.5 and 14.0 kg ha-1 of N, P, K, Ca, Mg and S were respectively accumulated. Forage turnip management at pre-flowering stage cause a quick straw degradation and macronutrients release. Potassium and nitrogen were released in the highest amounts and in the shortest time to the subsequent tillage. Quickest liberation of nutrients occurred between 10 to 20 days after plant management.